PENGARUH PANJANG SERAT DAN FRAKSI VOLUME TERHADAP KEKUATAN IMPACT DAN BENDING MATERIAL KOMPOSIT POLYESTER- FIBER GLASS DAN POLYESTER-PANDAN WANGI - Sulistyowati, Emmy Dyah; Sari, Nasmi Herlina; Yudhyadi, IGNK; Sinarep, S.; Topan, T. (Dinamika Teknik Mesin, 2012)
At this research by using two kinds of composite that is composite of fibre of screw pine of fragrant and composite of glass fibre. And in doing research will be done by two examination type that is test the strength bending and test the strength impact. How strength from two composite type of examinee with the long variation  and fibre volume to be used.As the result test the strength of impact and bending to be composite of screw pine of fragrant with the long variation of fibre with the random fibre direction that composite highest strength impact of fibre of screw pine of fragrant got at fibre length 5 cm of equal to 2286,67 singk / m². while for the variation  of volume of highest strength impact fibre there are at fibre volume 40% with the unidirectional fibre direction equal to 2940 Kj / m². While to result of composite strength bending test of screw pine of fragrant got by biggest strength bending with the long variation of fibre with the direction of fibre random, gotten at fibre length 5 cm of equal to 146,67 KN . while for the strength of bending with the variation of fibre volume with the unidirectional fibre direction, highest strength bending got at fibre volume 40% equal to 236,67 KN. Medium to result of composite strength impact test of glass fibre at long variation of highest strength fibre got at length seart 5 cm of equal to 5553,33 Kj / m². While strength impact with the variation of biggest strength fibre volume at fibre volume 40% with the unidirectional fibre direction equal to 15908,67 Kj / m². Medium at composite strength bending test of glass fibre with the long variation of fibre  where fibre direction is random of biggest kerkutan bending at fibre length 5 cm of equal to 263,33 KN. while to result of kekutan bending  at variation  of fibre volume got by biggest strength bending at fibre volume 40% equal to 278,34 KN.